2019
DOI: 10.1038/s41467-019-12997-7
|View full text |Cite
|
Sign up to set email alerts
|

Single-atom cobalt array bound to distorted 1T MoS2 with ensemble effect for hydrogen evolution catalysis

Abstract: The grand challenge in the development of atomically dispersed metallic catalysts is their low metal-atom loading density, uncontrollable localization and ambiguous interactions with supports, posing difficulty in maximizing their catalytic performance. Here, we achieve an interface catalyst consisting of atomic cobalt array covalently bound to distorted 1T MoS2 nanosheets (SA Co-D 1T MoS2). The phase of MoS2 transforming from 2H to D-1T, induced by strain from lattice mismatch and formation of Co-S covalent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
341
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 438 publications
(349 citation statements)
references
References 57 publications
7
341
1
Order By: Relevance
“…2e ). A slight discrepancy could be explained by the localized structural distortion due to the attachment of Pt atoms 20 , 21 . Moreover, analysis by STEM coupled with energy-dispersive X-ray spectroscopy (STEM-EDS) revealed that atomic Pt was homogeneously dispersed over the whole material (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2e ). A slight discrepancy could be explained by the localized structural distortion due to the attachment of Pt atoms 20 , 21 . Moreover, analysis by STEM coupled with energy-dispersive X-ray spectroscopy (STEM-EDS) revealed that atomic Pt was homogeneously dispersed over the whole material (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Considering these results, the reaction process driven by Rh doped CoFe-ZLDH follows the Volmer-Heyrovsky mechanism to achieve a rapidly increasing hydrogen evolution rate under the application of voltage. As shown in Figure 3c and Table S2 in the Supporting Information, Rh-doped CoFe-ZLDH outperforms many other previously reported state-of-art HER electrocatalysts, such as Rh 2 P, [41] L-Ag, [42] single atomic Co supported on phosphorized carbon nitride nanosheets (Co 1 /PCN), [43] NiMoO x -Ni(OH) 2 /NF, [44] interface catalyst consisting of atomic cobalt array covalently bound to distorted 1T MoS 2 nanosheets (SA Co-D 1T MoS 2 ), [45] Pt clusters in hollow mesoporous carbon spheres (Pt 5 /HMCS), [46] Ni-Fe nanoparticle (Ni-Fe NF), [39] oxygen vacancy enrich CoFe 2 O 4 (r-CFO), [47] CoFeP TAPs/Ni, [48] nickel-molybdenum-nitride nanoplates on carbon fiber cloth (Ni-Mo-N/CFC), [40] Ru SA -N-S-Ti 3 C 2 T x , [9] W-CoP NAs-CC, [49] MoP@NCHs-900, [50] Co 9 S 8 @C, [51] and Co 0.31 Mo 1.69 C/MXene/NC. [52] The cyclic voltammetry (CV) method was utilized to calculate the electrochemical double-layer capacitance (C dl ) to reflect the electrochemical active area (ECSA).…”
Section: Electrocatalytic Propertiesmentioning
confidence: 94%
“…Here, different synthetic strategies for single metal atom-doped MoS 2 are summarized and discussed ( Fig. 2a-f [36][37][38][39][40][41]).…”
Section: Synthesismentioning
confidence: 99%